AKTUALISASI NILAI-NILAI KONSTITUSI DALAM KEBIJAKAN PERDAGANGAN INDONESIA DI TINGKAT REGIONAL DAN MULTILATERAL - Dias Satria; Farah Wulandari (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
The purposes of this study were to analyze the implementation of the Indonesian con-stitutional values in Indonesia and in the regional level of trade policies (AFTA-ASEAN Free Trade Area). The method used is a qualitative approach. The findings ofthis research stated that there are some trade policy that misses thebasic values of the1945 Constitution and Pancasila, resulting inmismanagement in development policyand therefore contributesto lowering the level of public welfare in general. The policy,among others, is the policy of trade protection is not based on the principle of wealthcreation and equitable distribution, but is based on the behavior of crony-capitalism;government policiesrelated to foreign ownership in an investment is still not heedingthevalues and principles of broad benefit of welfare, justice andequity; and governmentprotection policies in the agriculturalsector is still not optimal to create a high com-petitiveness.Keywords: constitution, international trade, welfare and equity.